Trade Unions and Corporate Social Responsibility - Laszlo Goerke (ZBW - Leibniz Information Centre for Economics, 2020)
Trade unions distort a profit-maximising firm's input choice. The nature of the resulting inefficiency depends on whether there is wage or efficient bargaining. Moreover, trade unions redistribute income and thereby affect welfare. If firms also pursue Corporate Social Responsibility (CSR) objectives, input choices are distorted already in the absence of collective bargaining. Adopting a positive perspective, we show that CSR objectives which foster economic activity have ambiguous wage and employment consequences in case of wage negotiations and raise employment if there is efficient bargaining. Importantly from a normative vantage point, such CSR objectives make a welfare-enhancing role of trade unions more likely in the presence of wage negotiations, whereas the reverse may be true in case of efficient bargaining.
Keywords: D60; J51; L31; M14; 330; Corporate Social Responsibility; Efficient Bargaining; Trade Unions; Wage Bargaining; Welfare